The Implementation of Project-Based Learning in Higher Education: A Case Study in the Indonesian Context - Rachmawati, Umi; Pradita, Linda Eka; Ulyan, Mohammad; Sotlikova, Rimajon (Universitas Pendidikan Mandalika, 2024)
The implementation of project-based learning has been the center of the teaching and learning process in higher education especially in Indonesia. Higher degree education including universities that implements the project-based learning model. Along with the practical use in class, there is a need to clarify whether the project-based learning has been well conducted. This study is conducted through qualitative approach to dig depicted picture of the implementation of the teaching model. The data were gathered through observation and in-depth interview which were analyzed using qualitative data analysis. The observation covers the preparation of the class like checking the lesson plan, syllabus, learning materials, and the instructional model used. The observation has also been done during the implementation of the lesson plan. The in-depth interview was done through conducting interview with the lecturers and the students about the implementation of the instructional model. The result of the study presents that the implementation of project-based learning was done in a number of ways and stimulate the development of the students’ skills. The implementation of the model was done in various ways covering the three main processes: preparation, implementation, and evaluation. The model implemented facilitates the students’ problem-solving skills, critical thinking skills, communication skills, collaboration skills, and information literacy. As the students developed their life skills, the teaching through the project-based learning model can be done creatively depending on the learners’ and teacher’s characters and the learning facilities.